Efektifitas Program Tani Milenial di Kalurahan Pampang - Sayekti, Lulu; Wahyuni, RR.E. Anggraeni Eksi (Mahesa Research Center, 2023)
This article aims to describe the effectiveness of the Millennial Farmer Program in Pampang District and to find out what factors influence the effectiveness of the program. The problem is focused on the effectiveness of the Millennial Farmer Program in Pampang District. In order to approach this problem, Sutrisno (2007) uses the effectiveness theory reference, namely program understanding, target accuracy, timeliness, goal achievement, and tangible results. The data were collected through interviews, observation, and documentation and analyzed qualitatively. This study concludes that the Millennial Farmer Program in Pampang District has not been effective. The parties related to the Millennial Farmer Program do not understand the program well, the program targets/targets are not appropriate and do not meet the criteria, the timeliness is not in accordance with the program target time, the achievement of program objectives has not been effective, and there have been the realistic changes specifically felt by the participants and The Pampang District society in general. The factors that affect the effectiveness of the program are the lack of socialization from the government, the lack of commitmen, motivation and interest in millennial human resources in the agricultural sector, the lack of entrepreneurial activities from the program, and the lack of capital assistance from the government.